Bioseguridad del personal recolector de basura en el Municipio de Loja, periodo junio-noviembre del 2013 - Silva Vivanco, Guadalupe Yesenia (2014)
Biosecurity, created to reduce the risks that threaten the health and even the life of the individual, family and community that in recent years it has gained an extraordinary interest from the epidemic in what refers to both the population risks in general as of the workers who are in contact with pollutants. Faced with this social reality arises as I study this topic "Biosecurity staff collecting garbage in the municipality of Loja, in the period June - November of 2013." In order to characterize biosafety standards and compliance in the daily work. The study is descriptive, carried out in the Department of health of the municipality of Loja., the sample consisted of 136 workers, technique and instrument of data collection was the survey and the observation guide obtained the following results. The staff are in a higher percentage that they collect the garbage in the streets and a minimal relationship to staff working in collecting garbage trucks, there are more men and few women, in the same way they are married and have instruction primary most, most have been working less than five years, but there are also workers with 20 to 30 years of servicelittle is the staff that meet biosafety standards but not apply them, a very relevant piece of information personnel do not use disinfectant SOAP, and many of them are not immunized against hepatitis B, not maintain protective equipment in perfect condition, in the same way workers remains as protective household gloves so it can be deduced that the municipality of Loja does not provide them the necessary protective equipment.